High-test molasses or maize as an energy source for growing pigs. Status of digestive organs - Ly, Julio (Cuban Journal of Agricultural Science, 2016)
To study the status of digestive organs, sixteen pigs of commercial crossbreed, females and castrated males, in the same proportion, wereused, of about 55 kg of live weight, randomly divided into two groups. The animals after 30 kg were fed ad libitum, with diets of high-test molasses or maize, as only energy source, and torula yeast, as only protein source. There were no main effects of the interaction sex per diet, neither sex effect. The digestive tract was numerically lower and the large intestine was significantly less heavy (P< 0.05) in the treatment with high-test molasses (43.0 and 16.3g/kg of body weight), in contrast with the maize (46.6 and 20.0g/kg of body weight). Equally, in the high-test molasses diet, the percentage contribution was significantly (P< 0.05) lower (37.9%) than in the maize diet (43.0%). In pigs fed with high-test molasses/torula yeast, the liver weighed more (P>0.01) and the pancreas less (P< 0.001) than those fed with maize/torula yeast. It is suggested that there are differences in the gastrointestinal macro-architecture and accessory glands of the pigs in growth, fed with diets of high-test molasses, as only energy source.Key words: pigs, high-test molasses, gastrointestinal tract, morphometry